The Integrated Financial and Real System of National Accounts for the United States: Does It Presage the Financial Crisis? - Palumbo, Michael G; Parker, Jonathan A (American Economic Review, 2009)
The Integrated Financial and Real System of National Accounts for the United States: Does It Presage the Financial Crisis? by Michael G. Palumbo and Jonathan A. Parker. Published in volume 99, issue 2, pages 80-86 of American Economic Review, May 2009